Assessment of the Impact of Pretreatment of Spent Coffee Grounds with Diluted Sulfuric Acid on the Efficiency of Methane and Lactic Acid Fermentation - Gosławski, Sebastian (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
Lignocellulosic materials are composed of three major biocomponents such as cellulose, hemicellulose and lignin, which form a compact lignocellulosic complex. Characterized by high caloric content, lignocellulosic biomass, including coffee grounds, is a valuable energy source that can be efficiently used in various bioconversion and biotransformation processes. Due to the high consumption of coffee in the world, there is an increasing amount of coffee grounds, which is a rich waste and at the same time a valuable secondary raw material, and its use fits perfectly into a closed-loop economy. Coffee grounds biomass contains polysaccharides, mainly mannans, proteins, lipids, polyphenols, which will allow the development of different biorefinery strategies, the creation of new value-added products with reduced waste generation. The research describes the pre-treatment of coffee grounds with dilute sulfuric acid to evaluate the effect of acid concentration, hydrolysis time on biogas yield, including methane and lactic acid biosynthesis during anaerobic fermentations. A yield of 381.12 mL of CH4/g-VS methane was obtained, accounting for 72.48% of the total biogas composition. It was found that the most efficient sample in terms of substrate pre-treatment for lactic acid biosynthesis was coffee grounds after 90 min hydrolysis with 1.5% H2SO4 at 121 °C.